2017
DOI: 10.1117/1.nph.5.1.011010
|View full text |Cite
|
Sign up to set email alerts
|

Study of memory deficit in Alzheimer’s disease by means of complexity analysis of fNIRS signal

Abstract: Working memory deficit is a signature of Alzheimer's disease (AD). The free and cued selective reminding test (FCSRT) is a clinical test that quantifies memory deficit for AD diagnosis. However, the diagnostic accuracy of FCSRT may be increased by accompanying it with neuroimaging. Since the test requires doctor-patient interaction, brain monitoring is challenging. Functional near-infrared spectroscopy (fNIRS) could be suited for such a purpose because of the fNIRS flexibility. We investigated whether the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…Five significant differences were found in the right superior temporal gyrus, left middle temporal gyrus, right olfactory cortex, left inferior occipital gyrus, and right supramarginal gyrus (SMG.R) at scale factor six. Grieder et al [ 134 ] found that the AD group showed a lower global default mode network (DMN)-MSE than the NC group. A scientific explanation has been found for the reduced complexity of fMRI and fNIRS signals in AD.…”
Section: Resultsmentioning
confidence: 99%
“…Five significant differences were found in the right superior temporal gyrus, left middle temporal gyrus, right olfactory cortex, left inferior occipital gyrus, and right supramarginal gyrus (SMG.R) at scale factor six. Grieder et al [ 134 ] found that the AD group showed a lower global default mode network (DMN)-MSE than the NC group. A scientific explanation has been found for the reduced complexity of fMRI and fNIRS signals in AD.…”
Section: Resultsmentioning
confidence: 99%
“…In AD, it was utilized to analyze resting-state brain activity deriving from Magnetoencephalographic [ 34 ] and EEG signals [ 35 , 36 ]. Concerning fNIRS, SampEn was used to investigate cortical activation in AD patients during the administration of Free and Cued Selective Reminding Test [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies used entropy estimates in protocols of long time windows with unspecified timing of events in the signal, as in the case of cognitive capacity analysis in Alzheimer’s [ 21 , 22 , 23 ]. Nevertheless, regularity and complexity analyses of fNIRS signals during standard cognitive load tests, such as motor imagery and mental arithmetics, were not investigated to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Jin et al investigated permutation entropy to analyze differences in experts and novices solving science problems [ 20 ]. Studying frontal cortex fNIRS signals, SampEn was suggested as a biomarker for Alzheimer’s disease diagnosis [ 21 , 22 , 23 ], and Angsuwatanakul et al [ 24 ] investigated the effects of working memory experiments on SampEn estimated from fNIRS series. Also, though applied as an information theoretic approach to investigate linear effects in fNIRS rather than analyze topological entropy in phase space, differential entropy has been investigated in Keshmeri et al as a biomarker that preserves variational information in the assessment of working memory [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%